The Influence of Principal Leadership Style and Academic Supervision on Teachers’ Professional Competence in Public Elementary Schools - Setianto, Adi; Soedjono, Soedjono; Nugroho, Aryo Andri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the influence of principal leadership style and academic supervision on teachers’ professional competence in public elementary schools in Patean District, Kendal Regency. Employing a quantitative approach with an ex post facto survey design, data were collected from 149 teachers selected through proportional random sampling from a total population of 237 teachers across public elementary schools in Patean District. The primary data source consisted of teachers’ responses to validated Likert-scale questionnaires measuring three variables: principal leadership style, academic supervision, and teachers’ professional competence. Data analysis was conducted using IBM SPSS Statistics version 26, including Pearson product-moment correlation to assess the strength of relationships between variables, simple linear regression to determine the individual effect of each independent variable, and multiple linear regression to examine the simultaneous influence of both variables on teachers’ professional competence. Hypothesis testing was performed at a significance level of α = 0.05. The results revealed that principal leadership style had a significant positive influence on teachers’ professional competence, contributing 75.0% of the variance. Academic supervision also demonstrated a significant positive effect, accounting for 70.9% of the variance in teachers’ professional competence. Simultaneously, principal leadership style and academic supervision explained 81.2% of the variance in teachers’ professional competence, indicating a very strong and statistically significant combined effect. These findings emphasize the importance of effective school leadership and continuous academic supervision in strengthening teachers’ professional competence, improving instructional quality, and supporting sustainable educational development in elementary schools.